Seed health of stored lentil collected from major lentil growing areas of Bangladesh - Mahmud, JA; Ahmed, M; Adhikary, SK (Bangladesh Journal of Agricultural Research, 2019)
An experiment was conducted in the Plant Pathology Laboratory, Regional Agricultural Research Station, BARI, Jashore using 126 lentil seed samples collected from farmer’s store of different lentil growing areas of Bangladesh to determine physical status and fungal association with lentil seeds. The collected seeds contained different varieties and locations. The seeds were grouped into four grades according to physical status. Among the varieties the maximum apparently healthy seed i. e. grade-1 was found in BARI Masur-7 (90.92 %) and the minimum was in local (59.34 %) varieties. In respect of location the maximum grade-1 seed was recorded from Madaripur (90.75 %) and minimum in Kushtia (47.67 %) district. Germination percentage was the highest in BARI Masur-7 (94.00 %) and the lowest in BARI Masur-3 (75.42 %) variety. Among districts, the highest germination was found in seeds of Meherpur (89.83 %) and the lowest in Narail (62.97 %). A linear positive relation was found between percent germination and apparently healthy seed in case of both varieties and locations. Six fungal genera were associated with lentil seed samples viz. Fusarium sp., Alternaria sp., Stemphylium sp., Curvularia sp., Penicillium sp. and Aspergillus spp. Aspergillus niger caused highest infection (17.58 %) followed by Fusarium oxysporum, Alternaria tennuis, Stemphylium botryosum, Curvularia lunata, Penecillium sp., Aspergillus flavus, Aspergillus paraciticus and Aspergillus candidus and the lowest (4.67 %) by Aspergillus ocraceous. Average association of fungi was the highest in local variety (3.27 %) and it was the lowest in BARI Masur-7 (0.50 %). Bangladesh J. Agril. Res. 44(1): 59-68, March 2019